2010
DOI: 10.1680/geng.2010.163.6.343
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-cyclic loading strength of silica-grouted sand

Abstract: The aim of this study is to investigate whether there is a loss in the strength of fine-to medium-grained colloidalsilica-grouted sand after cyclic loading. First, the rheological properties of colloidal silica grouts, such as gel time and viscosity, are studied. Then, appropriate colloidal silica grouts (saline solution/colloidal silica suspension ratios of 10%, 15%, 20% and 25% by weight) are selected. The selected colloidal silica grouts are then injected into fine-to medium-grained sand specimens prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…Therefore, gel time can be defined as the time needed for a CS solution to evolve from gel state 1 to gel state 10 [40,45]. Since the relationship of gel time with pH value is not as clear as that with ionic strength, the salt concentration has always been adjusted to control the gel time in previous experimental studies in the literature [14,17,20,32,50]. Sodium chloride (NaCl) or calcium chloride (CaCl 2 ) has mostly been adopted as the electrolyte solution of choice to adjust salt concentration in order to start the gelation process.…”
Section: Gelling and Curing Process For Csmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, gel time can be defined as the time needed for a CS solution to evolve from gel state 1 to gel state 10 [40,45]. Since the relationship of gel time with pH value is not as clear as that with ionic strength, the salt concentration has always been adjusted to control the gel time in previous experimental studies in the literature [14,17,20,32,50]. Sodium chloride (NaCl) or calcium chloride (CaCl 2 ) has mostly been adopted as the electrolyte solution of choice to adjust salt concentration in order to start the gelation process.…”
Section: Gelling and Curing Process For Csmentioning
confidence: 99%
“…Mollamahmutoglu and Yilmaz (2010) performed a series of gel experiments with different salt concentrations and salt solution quantities, and the gel time curves for three magnitudes of salt concentrations were plotted against the addition quantities of the salt solution. It was concluded that gel time decreases with an increasing salt concentration and an increasing ratio of salt solution volume to CS volume [14]. Wong proposed that a 1.7 mol/L NaCl solution should be hand mixed with CS in a 1:5 ratio by volume to obtain a 1 h gel formation time [50].…”
Section: Gelling and Curing Process For Csmentioning
confidence: 99%
See 1 more Smart Citation
“…To date the mechanical 29 behaviour of grouted soils which has been reported has been largely limited to the undrained 30 behaviour of grouted sand. Unconfined compressive strength (UCS) tests of grouted soil 31 samples have been reported which demonstrate that grouted-sand specimens have UCS values 32 up to several hundreds of kPas and that increasing the concentration of silica in the colloidal 33 suspension increases the UCS and that UCS increases with curing time (Persoff et al, 1999, 34 Gallagher and Mitchell, 2002, Liao et al, 2003, Mollamahmutoglu and Yilmaz, 2010 Changizi and Haddad, 2017). Undrained triaxial tests have also been conducted which 36 demonstrate the reduced deformation of grouted sand specimens (and hence reduced loss of 37 strength) when subjected to cyclic loading (to simulate earthquake loading) as a means of 38 assessing its potential to mitigate against liquefaction (Gallagher and Mitchell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Mollamahmutoglu and Yilmaz (2010) investigate whether there is a loss in the strength of silicagrouted sand after cyclic loading. A range of silica grout type is injected into the sand and allowed to cure for different periods of time.…”
mentioning
confidence: 99%